Determinantes de vendas em E-commerce: estudo de perspectiva de marketeers sobre as estratégias de SEM, SEO, SEA e brand awareness - Santarelli, Bruna Lívia (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Driven Marketing, specialization in Marketing Intelligence